2019
DOI: 10.4062/biomolther.2019.135
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Regression via Integrative Regulation of Neurological, Inflammatory, and Hypoxic Tumour Microenvironment

Abstract: Changing trends in anticancer research have altered the treatment paradigm to the extent that it is difficult to investigate any anticancer drugs without mentioning immunotherapy. Thus, we are finally contemplating tumour regression using magic bullets known as immunotherapy drugs. This review explores the possible options and pitfalls in tumour regression by first elucidating the features of cancer and the importance of tumour microenvironments. Next, we evaluated the trends of anticancer therapeutics regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 112 publications
(129 reference statements)
0
17
0
Order By: Relevance
“…Nerve connection: The success of immune checkpoint drugs has confirmed the importance of the tumour microenvironment in the treatment area of cancer, and the importance of nerves associated with cancer has also recently been highlighted [158,159]. Many reports have shown that nerve elements are involved in tumour progression.…”
Section: Possible Role Of Anln On Other Hallmarks Of Cancermentioning
confidence: 99%
“…Nerve connection: The success of immune checkpoint drugs has confirmed the importance of the tumour microenvironment in the treatment area of cancer, and the importance of nerves associated with cancer has also recently been highlighted [158,159]. Many reports have shown that nerve elements are involved in tumour progression.…”
Section: Possible Role Of Anln On Other Hallmarks Of Cancermentioning
confidence: 99%
“…The published articles are based on neuro-oncological research and deal with proposing novel effective therapeutic strategies, focusing on different targets and aspects typical of brain tumors: tumor heterogeneity and microenvironment, cancer cell response to new chemotherapeutics and innovative radiotherapy treatments settings (often tested in combined protocols), immune-mediated gene therapies, which may involve blockade of immune checkpoint inhibitors, and other targeted therapies such virotherapy, CAR-T cells, dendritic cells' vaccines, The joint mechanisms of neuro-inflammation, tumor microenvironment and BBB leakage status, which have been shown to trigger the tumor onset, invasion and progression, often mediated by the deregulation of a number of channel proteins and ion pumps (Brandalise et al), have been also explored as promising targets for personalized pharmacological interventions (Alghamri et al;Di Cintio et al;Lee et al, 2020). Another exploited key mechanism is cell death, a crucial multifaceted process dependent on signal transduction pathways, in which several Hsp90 client proteins, frequently abnormally expressed, may be involved (Cao et al; Chen et al).…”
Section: Editorial On the Research Topic Brain Cancers: New Perspecti...mentioning
confidence: 99%
“…The joint mechanisms of neuro-inflammation, tumor microenvironment and BBB leakage status, which have been shown to trigger the tumor onset, invasion and progression, often mediated by the deregulation of a number of channel proteins and ion pumps ( Brandalise et al ), have been also explored as promising targets for personalized pharmacological interventions ( Alghamri et al ; Di Cintio et al ; Lee et al, 2020 ). Another exploited key mechanism is cell death, a crucial multifaceted process dependent on signal transduction pathways, in which several Hsp90 client proteins, frequently abnormally expressed, may be involved ( Cao et al ; Chen et al ).…”
mentioning
confidence: 99%
“…Nerves are an essential part of the tumour microenvironment and contribute to tumour progression [ 199 , 200 ]. For example, almost peripheral cancer types have been observed to interact with nerve structures at least at an advanced stage, especially in bladder cancer, prostate cancer, pancreatic cancer, colon cancer, lung cancer, head and neck cancer, and bile duct cancer [ 201 ].…”
Section: The Role Of Cdk5 In Cancer Cellsmentioning
confidence: 99%